Obstructive Sleep Apnea and Risk of COVID-19 Infection, Hospitalization and Respiratory Failure - Maas, Matthew B.; Kim, Minjee; Malkani, Roneil G.; Abbott, Sabra M.; Zee, Phyllis C. (Sleep & breathing, 2021)
Purpose To study the relationship between OSA and risk of COVID-19 infection and disease severity, identified by the need for hospitalization and progression to respiratory failure. Methods We queried the electronic medical record system for an integrated health system of 10 hospitals in the Chicago metropolitan area to identify cases of COVID-19. Comorbidities and outcomes were ascertained by ICD-10-CM coding and medical record data. We evaluated the risk for COVID-19 diagnosis, hospitalization, and respiratory failure associated with OSA by univariate tests and logistic regression, adjusting for diabetes, hypertension, and BMI to account for potential confounding in the association between OSA, COVID-19 hospitalization, and progression to respiratory failure. Results We identified 9405 COVID-19 infections, among which 3185 (34%) were hospitalized and 1779 (19%) were diagnosed with respiratory failure. OSA was more prevalent among patients requiring hospitalization than those who did not (15.3% versus 3.4%, p < 0.0001; OR 5.20, 95% CI (4.43, 6.12)), and among those who progressed to respiratory failure (19.4% versus 4.5%, p < 0.0001; OR 5.16, 95% CI (4.41, 6.03)). After adjustment for diabetes, hypertension, and BMI, OSA was associated with increased risk for hospitalization (OR 1.65; 95% CI (1.36, 2.02)) and respiratory failure (OR 1.98; 95% CI (1.65, 2.37)). Conclusions Patients with OSA experienced approximately 8-fold greater risk for COVID-19 infection compared to a similar age population receiving care in a large, racially, and socioeconomically diverse healthcare system. Among patients with COVID-19 infection, OSA was associated with increased risk of hospitalization and approximately double the risk of developing respiratory failure.